THE INFLUENCE OF SCIENTIFIC WORKS OF ACADEMICIAN AIDARKAN MOLDOKULOV ON THE DEVELOPMENT OF THE ECONOMY OF KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This year we celebrate the 95th anniversary of the outstanding Kyrgyz academician and activist Aydarkan Moldokulov. His contribution to economic science and practice cannot be overestimated, and his legacy continues to influence the development of the Kyrgyz economy. In this article, we will look at how A.Moldokulov’s scientific works influenced the country’s economic policy and how they can serve as a guide for the younger generation.
Keywords: Economy of Kyrgyzstan, science, management, scientists, development, contribution.